Comparison of Single Term Walsh Series Technique and Extended RK Methods Based on Variety of Means to Solve Stiff Non-linear Systems - Dhayabaran*, A. Emimal Kanaga Pushpam; D. Paul (Recent Research in Science and Technology, 2011)
This paper presents a comparison of Single Term Walsh Series (STWS) technique and the extended Runge-Kutta (RK) methods based on variety of means such as Arithmetic Mean (AM), Harmonic Mean (HaM), Centroidal Mean (CeM) and Contraharmonic Mean (CoM) to solve stiff non-linear systems of initial value problems (IVPs). Numerical solutions of some stiff non-linear systems are investigated for their stiffness. The discrete solutions obtained through STWS technique are compared with that of the RK methods based on variety of means. The applicability of the STWS technique has been demonstrated. The results show that the STWS technique is more suitable to solve stiff non-linear systems including highly stiff problems.